Urbanization and transport energy consumption in African countries - SATOGUINA, ONÉSIME HONORAT FLAVIEN; LOKONON, Boris O. K (My University, 2023)
Transport is of paramount importance for economic activities. However, transport energy use contributes to pollution, so generates negative externalities. This paper analyzes the relationship between economic development and the transport final energy consumption in African countries. The paper applies the panel threshold regression (PTR) model to test the validity of energy-environmental Kuznets curve (EKC) hypothesis for a panel of 25 African countries over the period 1992-2017. The findings show no evidence supporting the validity of energy-EKC hypothesis for transport energy use in Africa. Actually, the findings suggest that there is a significant positive relationship between total and per capita transport energy use and gross domestic product (GDP) per capita, and when GDP per capita exceeds a given threshold (US$ 903.774), its positive effect on total and per capita transport energy turns larger. Thus, economic development leads to more energy use for transportation, either per capita energy use or the total energy use. Therefore, the results from this study suggest that African countries should promote the use of the cleaner technologies that produce less pollution per unit of output in the transport sector.
Keywords: Transport; environmental Huznets curve; Energy Utilization; Externality; Africa